1984
DOI: 10.1111/j.1600-0609.1984.tb02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Staging and survival in multiple myeloma

Abstract: The records of 91 patients with multiple myeloma were reviewed and staging was performed according to Durie & Salmon (1). Patients with progressive disease were re‐staged. Patients first diagnosed in stage I were younger than patients first diagnosed in stage III and survived longer than patients in stages II or III. The duration of stage I was longer than the duration of stages II and III. When patients in stage I‐II progressed into stage III, their age and remaining survival time were similar to the age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the clinical staging system for multiple myeloma proposed by Dune and Salmon (l), easily available clinical data are used for the separation of myeloma patients into three stages, with low, intermediate, or large tumour cell mass. Several studies have confirmed the prognostic value of this staging system (2)(3)(4). Patients with impaired renal function in addition to a large tumour cell mass (stage IIIB) have the worst prognosis (1).…”
mentioning
confidence: 87%
“…In the clinical staging system for multiple myeloma proposed by Dune and Salmon (l), easily available clinical data are used for the separation of myeloma patients into three stages, with low, intermediate, or large tumour cell mass. Several studies have confirmed the prognostic value of this staging system (2)(3)(4). Patients with impaired renal function in addition to a large tumour cell mass (stage IIIB) have the worst prognosis (1).…”
mentioning
confidence: 87%